International Pallliative Care Seminar: BREASTFEEDING EFFECTIVELY REDUCE PAIN IN IMMUNIZED INFANT - Rahmah, Arief Dharma Kurniawan (2014)
Background: Immunization in infants is an action that can affect to trauma because it can cause pain. One of the techniques of non-pharmacological pain management is breastfeeding. The purpose of this study was to determine the effect of Breastfeeding on pain reduction in infant’s immunization.